2012
DOI: 10.1038/eye.2012.137
|View full text |Cite
|
Sign up to set email alerts
|

Estimating quality-adjusted life years from patient-reported visual functioning

Abstract: Purpose Glaucoma is an important disease, the impacts of which on vision have been shown to have implications for patients' health-related quality of life (HRQoL). The primary aim of this study is to estimate a mapping algorithm to predict EQ-5D and SF-6D utility values based on the vision-specific measure, the 25-item Visual Functioning Questionnaire (VFQ-25), as well as the clinical measures of visual function, that is, integrated visual field, visual acuity, and contrast sensitivity. Methods Ordinary least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…These issues, however, are mainly directed at the suitability of OLS for predicting EQ-5D utility scores due its bi-or often tri-modal distribution [29] and the well documented ceiling effect of the instrument [30,31], which typically results in a concentration of observations at 1. A number of studies have found OLS to be appropriate when mapping to the SF-6D, often finding this method to demonstrate superior performance to alternatives such as Tobit, CLAD, two-part models and response mapping methods in this context [32][33][34]. The distribution of the SF-6D scores in both the estimation and validation data sets were therefore tested for normality in order to assess the appropriateness of OLS to model this particular relationship.…”
Section: Discussionmentioning
confidence: 99%
“…These issues, however, are mainly directed at the suitability of OLS for predicting EQ-5D utility scores due its bi-or often tri-modal distribution [29] and the well documented ceiling effect of the instrument [30,31], which typically results in a concentration of observations at 1. A number of studies have found OLS to be appropriate when mapping to the SF-6D, often finding this method to demonstrate superior performance to alternatives such as Tobit, CLAD, two-part models and response mapping methods in this context [32][33][34]. The distribution of the SF-6D scores in both the estimation and validation data sets were therefore tested for normality in order to assess the appropriateness of OLS to model this particular relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Although the MAE, MSE, and RMSE are criteria for evaluating model performance, we present the models that have the lowest RMSE. This is because the RMSE is measured in the same units as the data, is representative of the size of a 'typical' error, and is more sensitive than other measures to the occasional large error'' [33].…”
Section: Item 13: Measures Of Model Performancementioning
confidence: 99%
“…CS has become more important for quality of life assessments, which have been receiving increase attention in recent years (37)(38)(39) . CS is involved with differentiating low-contrast objects, such as human faces, and recognizing movement (37,40) .…”
Section: Discussionmentioning
confidence: 99%
“…Keywords: Macular degeneration; Contrast sensitivity; Glaucoma; Age effect; Repro ducibility of results , glaucoma, catarata e AMD foram, respectivamente, ICC 0,87; 0,90; 0,76; 0,69, e COR 0,24; 0,20; 0,38; 0,25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation